2019
DOI: 10.1212/wnl.0000000000007314
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of teriflunomide and dimethyl fumarate

Abstract: ObjectiveTo compare on-treatment efficacy and discontinuation outcomes in teriflunomide (TFL) and dimethyl fumarate (DMF) in the treatment of relapsing-remitting multiple sclerosis (RRMS) in a real-world setting.MethodsWe identified all patients starting TFL or DMF from the Danish Multiple Sclerosis Registry and compared on-treatment efficacy outcomes between DMF using TFL, adjusted for clinical baseline variables and propensity score-based methods.ResultsWe included 2,236 patients in the study: 1,469 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 28 publications
(32 reference statements)
7
40
0
Order By: Relevance
“…their age was 40 years on average, they were mostly female and had an annual rate of relapses of 0.13 during the pre-index period. These ndings are consistent with those of other studies 4,[6][7][8]22,23 . Conversely, some baseline characteristics differed between DMF and FTY patients, although their age at treatment initiation was very similar.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…their age was 40 years on average, they were mostly female and had an annual rate of relapses of 0.13 during the pre-index period. These ndings are consistent with those of other studies 4,[6][7][8]22,23 . Conversely, some baseline characteristics differed between DMF and FTY patients, although their age at treatment initiation was very similar.…”
Section: Discussionsupporting
confidence: 94%
“…Many observational studies have been used to assess the real-world comparative effectiveness of DMF and a number of alternative treatments, using claims based-analyses or registries with mixed results. The variability of these results may be explained by the various durations of follow-up limited to 1 year in some studies [3][4][5] , or by the use of simple propensity score (PS)-based methods in other studies 3,[5][6][7][8][9][10] , which although they can balance observed baseline covariates between groups, do nothing to balance unmeasured characteristics and confounders. In this context, comparative studies from real world practice in large population-based healthcare databases using robust statistical methods to handle confounders are needed to provide valuable evidence that will help clinicians in the choice of treatment.…”
Section: Introductionmentioning
confidence: 99%
“… Reduced disease activity in MS patients treated with dimethyl fumarate compared with patients treated with teriflunomide (Buron et al, 2019). Natalizumab and fingolimod had equal clinical effect in RRMS (Koch‐Henriksen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the pooled phase-III trial data from 14 mg of teriflunomide and dimethyl-fumarate (DMF) (TEMSO/TOWER vs. DEFINE/CONFIRM) revealed similar numbers needed to treat (NNT) to prevent one relapse or worsening disability (121, 138). However, in a recent registry-based study, the ARR was ~49% lower in patients treated with DMF, and teriflunomide treatment was associated with an increased risk of first relapse and increased incidence of discontinuation due to disease breakthrough (139). In another recent registry-based study with large patient populations, the ARR was similar between teriflunomide and DMF, and discontinuation rate was also similar; nevertheless, ARR were lower in patients treated with fingolimod compared to both DMF and teriflunomide, while disability accumulation was the same (140).…”
Section: Teriflunomidementioning
confidence: 99%